ATL. Issue 5 (1st June 2013) - Secord, Angeles Alvarez; Barnett, Jason Cory; Ledermann, Jonathan A.; Peterson, Bercedis L.; Myers, Evan R.; Havrilesky, Laura J.
Abstract : Objectives: (1) To determine whether use of a PARP inhibitor or (2) BRCA1/2 mutation testing followed by a PARP inhibitor for test positives is potentially cost-effective for maintenance treatment of platinum-sensitive recurrent high-grade serous ovarian cancer. Methods: A modified Markov decision analysis compared 3 strategies: (1) observe; (2) olaparib to progression; (3) BRCA1/2 mutation testing; treat mutation carriers with olaparib to progression. Progression-free survival and rates of adverse events were derived from a phase 2 randomized trial. Key assumptions are as follows: (1) 14% of patients harbor a BRCA1/2 mutation; (2) progression-free survival of individuals treated with olaparib is improved for BCRA1/2 carriers compared with noncarriers (estimated hazard ratio, approximately 0.4). Costs derived from national data were assigned to treatments, adverse events, and BRCA1/2 test. Monte Carlo probabilistic sensitivity analysis was performed. Results: Global olaparib was the most effective strategy, followed by BRCA1/2 testing and no olaparib. BRCA1/2 testing had an incremental cost-effectiveness ratio (ICER) of $193, 442 per progression-free year of life saved (PF-YLS) compared to no olaparib, whereas global olaparib had an ICER of $234, 128 per PF-YLS compared to BRCA1/2 testing. At a 52% lower-than-baseline olaparib cost estimate of $3000 per month, BRCA1/2 testing became potentially cost-effective compared with observation, with an ICER of $100, 000 per PF-YLS. When strategy (1) was removed from the analysis, BRCA1/2 testing was the preferred strategy. Conclusions: The use of maintenance olaparib in women with high-grade serous ovarian cancer is not cost-effective regardless of whether BRCA1/2 testing is used to direct treatment. However, BRCA1/2 testing is a preferred strategy compared to global maintenance olaparib alone.